[Memo from Samuel Chilcote, Jr. to Executive Committee, The Tobacco Institute regarding hearings on excise taxes and advertising limitations] - CHILCOTE,SD JR (Tufts Archival Research Center, 2007)
Missing Attachments; Memo from Samuel D. Chilcote, Jr. to Tobacco Institute Executive Committee, July 7, 1987. Provides update on the House Ways & Means Committee public hearings on options to increase revenues. Includes witness list and statements regarding excise taxes and advertising limitations. Lists higlights of the first day of hearings.